Azadirachtin blocks the calcium channel and modulates the cholinergic miniature synaptic current in the central nervous system of Drosophila. Issue 7 (24th October 2013) - Qiao, Jingda; Zou, Xiaolu; Lai, Duo; Yan, Ying; Wang, Qi; Li, Weicong; Deng, Shengwen; Xu, Hanhong; Gu, Huaiyu
Abstract BACKGROUND Azadirachtin is a botanical pesticide, which possesses conspicuous biological actions such as insecticidal, anthelmintic, antifeedancy, antimalarial effects as well as insect growth regulation. Deterrent for chemoreceptor functions appears to be the main mechanism involved in the potent biological actions of Azadirachtin, although the cytotoxicity and subtle changes to skeletal muscle physiology may also contribute to its insecticide responses. In order to discover the effects of Azadirachtin on the central nervous system (CNS), patch‐clamp recording was applied to Drosophila melanogaster, which has been widely used in neurological research. RESULTS Here, we describe the electrophysiological properties of a local neuron located in the suboesophageal ganglion region of D. melanogaster using the whole brain. The patch‐clamp recordings suggested that Azadirachtin modulates the properties of cholinergic miniature excitatory postsynaptic current (mEPSC) and calcium currents, which play important roles in neural activity of the CNS. The frequency of mEPSC and the peak amplitude of the calcium currents significantly decreased after application of Azadirachtin. CONCLUSION Our study indicates that Azadirachtin can interfere with the insect's CNS via inhibition of excitatory cholinergic transmission and partly blocking the calcium channel. © 2013 Society of Chemical Industry